Comparing fuel additives for fireside corrosion inhibition in pulverised fuel boilers using thermodynamic modelling. (September 2021) - Yelland, Thomas S.; Daood, Syed Sheraz; Nimmo, William
Abstract: This study presents a method for comparing corrosion inhibiting fuel additives using the thermodynamic modelling software FactSage TM . Two biomass ashes were investigated while using a range of loadings of three additives: Fe-based additive and two coal ashes, one with an 80% Si and Al contents and one with less than 50% of Si and Al contents but having a significant Ca content. The metrics used for analysis were the formation of various corrosive compounds and by-products. The Fe-based additive could inhibit the formation of corrosive species but not as well as either of the coal ashes, as it was key to increase the Si and Al content of the deposits. The coal ash with the greatest Si and Al content proved most capable of inhibiting fireside corrosion, while the contaminants present in the other coal ash proved detrimental to reducing the production of certain corrosive species. This method can be used as a qualitative predictive tool by research and development teams to quickly and economically understand the consequences of utilising fuel additives on ash chemistry or of changes in proportion/sources of fuel in a power plant. Highlights: A study to compare the biomass ash deposits' corrosivity using equilibrium modelling is presented. A range of fuel additives are compared for their corrosion inhibiting ability. Coal ashes are shown to be effective additives for minimising corrosion. The impact of contaminants in these fuel additives is discussed.